Weed control in oil palm nursery polybag using rice husk mat / Muhammad Ammar Yunus - Yunus, Muhammad Ammar (2023)
Weed management is an essential part of nursery maintenance for four- to twelvemonth-old oil palm seedlings. Monthly basis hand weeding is performed in polybags to ensure the absence of weeds and the production of high-quality oil palm seedlings. This conventional method is effective, but it is time-consuming and labour-intensive, resulting in high maintenance expenditures. Rice husk is an agricultural by-product of the rice milling process. It has been demonstrated that rice husk suppresses weeds, but its potential for weed management in polybag nurseries remains unknown. Thus, the objectives of this study were to 1) determine the effective thickness of rice husk mulch mat for weed control; 2) examine the effects of watering amounts on the physical and degradable properties of a rice husk mulch mat; and 3) evaluate the effectiveness of rice husk mulch mat for weed control in oil palm seedlings. In the rain shelter experiment, increasing the thickness of the mat from 2 to 8 mm reduced weed seedling emergence, coverage, and biomass six weeks after treatment. The 8 mm thick mat was the best thickness, since it completely inhibited the germination of Eleusine indica, Ageratum conyzoides, and Cyperus distans. Under rain shelter condition, the 8 mm thick mat was then treated to varying watering quantities per polybag for four months. The mats' biomass, thickness and diameter decreased by 43, 27, and 12%, respectively, when the watering regime was increased from 0 to 16 mm. The findings were supported by scanning electron microscopy and Fourier transform infrared spectroscopy analyses, which revealed a high rate of degradation of both rice husk and polyvinyl alcohol in mats subjected to a 16 mm watering regime.